Development of Digital Learning Media in Informatics Vocational Education in Facing the Industrial Revolution 4.0 (2003–2023) - Faizatul Amalia; Fitra Bahtiar (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2026)
The large number of digital learning media developed made researchers conduct this research. The objects of the study is to determine the extent of research trends on digital learning media in vocational schools, and the types of digital learning media that are most widely used. This study used the traditional literature review method. The tools used to obtain articles on the theme of digital learning media are Publish or Perish (PoP) and Scopus for the analysis using descriptive analysis. By entering the title and keywords in the PoP and Scopus applications, 44 articles were obtained and filtered. Based on the filtering process, 16 articles were mapped by specific topics: informatics vocational schools, and publications in relevant journals. The publication trend on digital learning media started in 2006, 2013, 2016, 2018, 2019, 2021, 2022, and 2023 and peaked in 2021. The types of digital learning media used in vocational schools include e-learning, e-books/flipbooks/e-modules, Augmented Reality, Android applications, and podcasts.